Thermodynamics. - Kumar, Prasanna (2013)
Designed for undergraduate students of mechanical engineering, this book offers a lucid treatment of the concepts dealt with in their core paper on Thermodynamics. It is an easily readable and compact textbook that covers all the topics that are relevant to a basic course on thermodynamics without any let up on academic rigor required for a thorough understanding of the subject.
12.1 Introduction.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books